ACCESS TO DRINKING WATER IN THE AMAZON REGION OF PARÁ: A COMPARATIVE ASSESSMENT BETWEEN THE STATE OF PARÁ AND THE MUNICIPALITY OF PARAGOMINAS-PA BASED ON QUALITY AND AVAILABILITY INDICATORS - Anaisse, Clarissa Campos Ribeiro; Puget, Lucas França; Moraes, Valéria Monteiro Carrera; Ribeiro, Hebe Morganne Campos; Lima, Alberto Carlos de Melo (Seven Editora, 2026)
Access to potable water in Brazil is significantly unequal, a reality that intensifies in the state of Pará, located in the Amazon region of Pará. This study aims to quantitatively analyze water accessibility in the state, with an emphasis on comparing the municipality of Paragominas-PA with other municipalities in Pará. The methodology was based on the analysis of secondary data from the National Sanitation Information System (SNIS), the National Basic Sanitation Survey (IBGE), and reports from the National Water Agency (ANA), in addition to the application of perception questionnaires to 40 participants from the municipality of Paragominas. The results show that, although the overall coverage rate is low, Paragominas stands out with a high percentage of service (95.75%), similar to the capital Belém. User perception indicated a high level of satisfaction (ISA = 1.00), but low confidence in direct water consumption (ICC = 0.3), revealing a contradiction between the regularity of supply and confidence in direct consumption. It is concluded that, despite some progress, significant social inequalities related to service reliability persist, requiring integrated public policies, structural investments, and communication strategies to strengthen public trust. Thus, this study contributes to the water supply in Pará, ensuring the human right to access water. Objective: The objective of this study is to analyze access to potable water in the state of Pará, based on data from official sources, by comparing water supply indicators in the municipality of Paragominas-PA, the capital city of Belém, and other municipalities in Pará, aiming to assess the percentage of the population served and identify challenges and possibilities for expanding access to treated and safe water. Theoretical Framework: Access to treated water and basic sanitation was recognized in 2010 by the United Nations (UN) as a fundamental human right, indispensable to guaranteeing the dignity, health, and well-being of the population. This recognition represents a significant normative milestone, guiding the formulation of public policies aimed at reducing inequalities in access to water supply and basic sanitation services. Within this context, the role of the Sustainable Development Goals (SDGs) stands out, especially SDG 6, which establishes as a goal ensuring the availability and sustainable management of water and sanitation for all. This guideline reinforces the importance of studies that analyze the conditions of access to drinking water, especially in the Amazon region, which is still marked by social inequalities. The unequal distribution of social services remains a major difficulty. Equity in access is a condition for the well-being of the population. At this point, it is possible to assess the importance of water governance, playing a significant role in Brazil and in the State of Pará, in a way that can guide the organization of supply systems and the formulation of new public policies focused on water resources, so that social justice can begin to bear fruit related to equal access. Currently, water resource governance in Pará relies on the National Basic Sanitation Policy (Law 11.445/2007); the National Water and Basic Sanitation Agency (ANA); the State Secretariat for the Environment (SEMAS-PA); the State Water Resources Commission; the Basin Committee; and the Pará Sanitation Company (COSANPA). Therefore, this study is of paramount importance for contributing to public policies, with improvements focused on access to water and water governance in the state as a whole. It is also an important topic to be discussed in the academic world. Method: This study is characterized as a mixed-methods research (quantitative and qualitative), with exploratory and descriptive objectives, focused on access to drinking water in the state of Pará. The quantitative phase was based on the collection and analysis of secondary data from official databases, including the National Sanitation Information System (SNIS), the National Basic Sanitation Survey (PNSB), conducted by the Brazilian Institute of Geography and Statistics (IBGE), and reports from the National Water and Basic Sanitation Agency (ANA). Additionally, a documentary analysis of Ordinance GM/MS No. 888/2021, which establishes the potability standards for drinking water in Brazil, was carried out to support the discussion on the quality and safety of distributed water. The qualitative phase consisted of conducting field research in the municipality of Paragominas-PA, through the application of a structured questionnaire to the local population. The sample consisted of 40 participants selected by convenience in a public place with high traffic. The instrument included questions related to the perception of water quality, regularity of supply, and level of satisfaction with the services provided. Quantitative data were analyzed using descriptive statistics, with calculation of frequencies and percentages, allowing for comparison between the evaluated indicators. For the analysis of qualitative data, a descriptive approach was adopted, seeking to identify patterns of user perception. In addition, two synthetic indicators were developed: the Supply Satisfaction Index (ISA) and the Consumption Confidence Index (ICC), with the objective of measuring, respectively, the level of user satisfaction with the service provided and confidence in the direct consumption of water. These indicators range from 0 to 1, with values ​​closer to 1 indicating better evaluation conditions. Results and Discussion: The results obtained show a predominantly positive perception on the part of the participants regarding the quality and distribution of water supplied in the municipality of Paragominas-PA. Most respondents expressed satisfaction with the services provided by the municipal authority, indicating that the water supply has generally met basic demands. Research Implications: The research presents relevant implications for basic sanitation and water resource management by highlighting inequalities in access to drinking water in the state of Pará. The results indicate the need to improve public policies, both in terms of expanding coverage and strengthening public confidence in the quality of the distributed water. The proposed indicators, such as the Water Supply Satisfaction Index (ISA) and the Consumption Confidence Index (ICC), prove to be useful tools for monitoring and decision-making, contributing to more efficient and appropriate strategies for the local reality. Originality/Value: The study contributes to the literature by offering an updated quantitative analysis of accessibility to treated water in the State of Pará through official data and theoretical references on the human right to water, social justice, and water governance.